Effect of nitrogen and phosphorus fertilizers on growth and biochemical composition of tomato (Solanum lycopersicum) - HANAN AMEER ABDULLAH (Smujo International, 2025)
Abstract. Abdullah HA. 2025. Effect of nitrogen and phosphorus fertilizers on growth and biochemical composition of tomato (Solanum lycopersicum). Asian J Agric 9: 507-512. Tomato (Solanum lycopersicum) is an economically important horticultural crop whose growth and quality are strongly influenced by nutrient management. Nitrogen (N) and phosphorus (P) are essential macronutrients that regulate plant metabolism, yet their combined effects on tomato performance under arid greenhouse conditions remain insufficiently explored. This study evaluated the interactive influence of ammonium sulfate and triple superphosphate on vegetative growth and biochemical composition of tomato. A completely randomized factorial design was applied with 16 N×P treatment combinations and three replications using 4 kg of soil per pot. Fertilizers were supplied in two equal splits at 10 and 25 days after seedling emergence, and plant responses were assessed after 52 days. Measurements included plant height, root length, shoot and root dry weights, leaf area, and concentrations of carbohydrates and proteins. Statistical analysis using two-way ANOVA and Duncan’s test (p?0.05) showed significant main and interactive effects of N and P. The combined application of 0.250 kg/ha N and 0.150 kg/ha P produced the best performance, with plant height nearly doubling compared to controls and protein content increasing by about one third. The synergistic effects of N and P were linked to enhanced photosynthetic capacity, stronger root development, and more efficient nutrient assimilation. These findings suggest that balanced fertilization strategies can improve both growth and nutritional quality of tomato while providing guidance for sustainable crop production in arid agroecosystems such as Iraq.